2020
DOI: 10.1016/j.healthpol.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

New integrated care models in England associated with small reduction in hospital admissions in longer-term: A difference-in-differences analysis

Abstract: Highlights Integration policies are often seen as strategies to reduce avoidable hospital activity. “New care models” were piloted in England under the “Vanguard” initiative. We evaluate the efficacy of the Vanguard programme in reducing hospital utilisation. The Vanguard initiative slowed the rise in emergency admissions observed in England. The reduction occurred mainly in care home sites, at the programme’s end.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 20 publications
2
57
0
Order By: Relevance
“…24 An analysis of a pooled sample of all 23 populationbased Vanguard models also found no significant reduction in emergency admissions over three years in total, although there was some evidence of a relative net reduction compared to controls in the third year. 25 This points to possible improvements over the longerterm, but the findings are not comparable on the precise measures we used in our analysis.…”
Section: Results In Contextmentioning
confidence: 81%
“…24 An analysis of a pooled sample of all 23 populationbased Vanguard models also found no significant reduction in emergency admissions over three years in total, although there was some evidence of a relative net reduction compared to controls in the third year. 25 This points to possible improvements over the longerterm, but the findings are not comparable on the precise measures we used in our analysis.…”
Section: Results In Contextmentioning
confidence: 81%
“…First, we were not able to account for local contextual factors which might have affected the adoption and implementation of integration processes. Moreover, implemented initiatives were heterogeneous across sites and difficult to describe in detail using interviews and documentary analysis [15,19,[32][33][34][35][36][37]. A recent evidence synthesis of 115 local Vanguard evaluation reports concluded that none of the reports offered "explanations and/or nuanced insights into the Vanguard operation" [38], making crossinitiatives comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
“…An intensive support programme led by NHSE was established to facilitate the development and spread of new models of care within and beyond the Vanguards, with the following elements [17]:…”
Section: New Care Model Vanguard Programme 2015-18mentioning
confidence: 99%
See 2 more Smart Citations